2013
DOI: 10.1016/j.chemosphere.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and environmental implications of pharmaceuticals in Chinese municipal sewage sludge

Abstract: h i g h l i g h t sPharmaceutical residuals were analyzed for sludge samples from 45 sewage treatment plants in China. Fluoroquinolone and tetracycline were the dominant antibiotics. Other pharmaceuticals such as ketoprofen and ibuprofen also in significant presence. Poor agreement found between the detected and predicted concentrations. t r a c tThe presence of pharmaceuticals in aquatic environment has become a topic of concern because of their potential adverse effects on human health and wildlife species.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(42 citation statements)
references
References 51 publications
5
36
1
Order By: Relevance
“…Diclofenac results corroborates a previous German study (Ternes et al, 2005), while other countries reported lower amounts (Martin et al, 2012;Jelic et al, 2011;Chen et al, 2013;Nieto et al, 2010;Okuda et al, 2009;Peysson and Vulliet, 2013;Radjenovic et al, 2009;Rodriguez-Rodriguez et al, 2011). The ibuprofen level corresponds to several Spanish studies (Nieto et al, 2010;Radjenovic et al, 2009;Rodriguez-Rodriguez et al, 2011), while another study reported a 20-fold higher concentration (Martin et al, 2012) in primary sludge.…”
Section: Occurrence Of Pharmaceuticals In Sewage Sludgesupporting
confidence: 88%
See 2 more Smart Citations
“…Diclofenac results corroborates a previous German study (Ternes et al, 2005), while other countries reported lower amounts (Martin et al, 2012;Jelic et al, 2011;Chen et al, 2013;Nieto et al, 2010;Okuda et al, 2009;Peysson and Vulliet, 2013;Radjenovic et al, 2009;Rodriguez-Rodriguez et al, 2011). The ibuprofen level corresponds to several Spanish studies (Nieto et al, 2010;Radjenovic et al, 2009;Rodriguez-Rodriguez et al, 2011), while another study reported a 20-fold higher concentration (Martin et al, 2012) in primary sludge.…”
Section: Occurrence Of Pharmaceuticals In Sewage Sludgesupporting
confidence: 88%
“…Carbamazepine concentration ranged between b LOQ and 410 μg/kg DM in this study. Martin et al (2012) reported similar loads, other studies reported lower values (Jelic et al, 2011;Chen et al, 2013;Nieto et al, 2010;Okuda et al, 2009;Peysson and Vulliet, 2013;Radjenovic et al, 2009;Rodriguez-Rodriguez et al, 2011). Sulfamethoxazole remained below the LOQ of 15 μg/kg DM in this study, while another German study reported up to 113 μg/kg DM (Gobel et al, 2005).…”
Section: Occurrence Of Pharmaceuticals In Sewage Sludgesupporting
confidence: 63%
See 1 more Smart Citation
“…The activated sludge process produces a large amount of sludge that causes a serious problem for pollution control. Pharmaceutical sludge, considered as a major, complex, and toxic industrial waste, contains relatively high levels of suspended solids, soluble organics, heavy metals, and recalcitrant antibiotics (Kaya et al, 2013), such as berberine hydrochloric (McClellan and Halden, 2010) and benzylpenicillin (Chen et al, 2013). The treatment and disposal fees for this type of sludge are very high (Yin et al, 2015) and can account for 25-65% of the total plant operation costs (Liu, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The studies on their presence in river sediments and soil (Vazguez-Roig et al 2010;Köck-Schulmeyer et al 2013), as well as sewage sludge (Radjenović et al 2009;Chen et al 2013) are less frequent, primarily due to the matrix complexity. The results have shown that these compounds were even found in the environment of the countries with strict law regulations on their residues and extensive waste water treatment.…”
Section: Introductionmentioning
confidence: 99%